Postcolonial Ecologies: The Cross-Pollination of Postcolonial and Environmental Studies - Perez Trujillo, Axel (The Trumpeter, 2016)
This paper will argue in favour of an intersection of interests between postcolonial and environmental studies, a convergence built on the relevance of hegemony in fully understanding the notion of place espoused by environmentalists. It explores the issues outlined by Richard Nixon's Slow Violence and the Environmentalism of the Poor (2011), discussing the challenges and advantages of combining both theoretical frameworks in an attempt to deepen our understanding of place.